Real-time Wavelet-Based Inline Banknote-in-Bundle Counting for Cut-and-Bundle Machines - Petker, Denis; Türke, Thomas; Willeke, Harald; Schaede, Johannes; Gillich, Eugen; Lohweg, Volker (IST/SPIE Electronic Imaging 2011 Conference)
Automatic banknote sheet cut-and-bundle machines are widely used within the scope of banknote production. Beside the cutting-and-bundling, which is a mature technology, image-processing-based quality inspection for this type of machine is attractive. We present in this work a new real-time Touchless Counting and perspective cutting blade quality insurance system, based on a Color-CCD-Camera and a dual-core Computer, for cut-and-bundle applications in banknote production. The system, which applies Wavelet-based multi-scale filtering is able to count banknotes inside a 100-bundle within 200-300 ms depending on the window size.